Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Bagian Gaji Dan Tata Usaha Biro Umum Sekretariat Jenderal Kementerian Kesehatan Republik Indonesia - Nur Hasanudin; Aryo Santiko (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research aims to determine partially or simultaneously the effect of work discipline and work motivation on employee performance in the Payroll and Administration Division of the General Bureau of the Secretariat General of the Ministry of Health of the Republic of Indonesia. The research method used in this research was quantitative research. The sampling technique used was simple random sampling and the sample was taken from 30 respondents. This research employed validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, coefficient of determination, F test and t test. Based on the results of the research, the t value for the work discipline variable on employee performance is 1.817 < t table 2.052. Therefore, it can be concluded that the work discipline variable has no significant effect on employee performance. The calculated t value for the work motivation variable on employee performance is 3.185 > t table 2.052. Therefore, it can be concluded that the work motivation variable has a significant effect on employee performance. The calculated F value is greater than F table (16.689 > 3.32) with a significance value of 0.000. It can be concluded that the variables of work discipline and work motivation simultaneously have a significant effect on employee performance. The results obtained is that the adjusted coefficient of determination R2 is 0.520. This shows that the variables of work discipline and work motivation simultaneously affect employee performance by 52%, while the remaining 48% is influenced by other factors not examined in this research.